Threats to Belonging—Stressful Life Events and Mental Health Symptoms in Aging Men—A Longitudinal Cohort Study - Lindert, Jutta; Lee, Lewina O.; Weisskopf, Marc G.; McKee, Martin; Sehner, Susanne; Spiro, Avron (Frontiers in Psychiatry, 2020)
Objectives: Stressful life events, especially relationship events, are frequent in adult life. We investigated the impact of a variety of stressful life events on symptoms of depression, anxiety, and hostility. Methods: We analyzed data from a large prospective cohort study of men (n=1,437) in the Boston area (assessed in 1985, 1988 and 1991). Main outcomes were measures of depression, anxiety and hostility symptoms. We used the Elders Life Stress Inventory (ELSI) to measure stressful life events in the past 12 months and examine their association with symptoms of depression, anxiety and hostility. First, we analyzed the association of stressful life events with symptom changes; second, we categorized stressful life events into finance/work-, health-, relationships-, loss-, living situations events; and third, we estimated the specific association between relationship events and depression, anxiety and hostility symptoms using multilevel models. Results: The most frequent stressful life events were health, relationship, and financial events. Depression, anxiety, and hostility symptoms were relatively stable among men who did not experience these life events. However, those who reported life events in the past 12 months had a greater increase in symptoms of depression (+0.05; 95% CI: 0.01 to 0.10) and of hostility (+0.05; 95% CI: 0.01 to 0.09) than those who did not. Additionally, we found a significant decrease in hostility (-0.05; 95% CI: -0.08 to -0.01) in those experiencing no life events.